184 President Oral Presentation Pick: Supplementation of Angus crossbred steers with avian-derived polyclonal antibody preparations against ruminal methanogenic Archaea alters ruminal fermentation and decreases ex situ methane production. (30th November 2020) - Garcia-Ascolani, Mariana E; Ruiz-Moreno, Martin; Schulmeister, Tessa M; Tarnonsky, Federico; Roskopf, Sergio; Podversich, Federico; da Silva, Gleise Medeiros; Martinez, Juan Vargas; Hackmann, Timothy J; Batista Dubeux, Jose Carlos; DiLorenzo, Nicolas
Abstract: An experiment was conducted to evaluate the effect of supplementing fourteen ruminally cannulated Angus crossbred steers with polyclonal antibody preparations (PAP) from avian origin against ruminal methanogens Methanobrevibacter gottschalkii Ho (PAP-Ho) and M. ruminantium M1 (PAP-M1). Steers were fed bermudagrass hay ad libitum and 2 kg d -1 of corn gluten feed. A randomized block design was used, with a 3 × 2 + 1 factorial arrangement, replicated in three periods. Factors were proportions of PAP against Ho and M1 in the mixture (100:0, 50:50, and 0:100 Ho:M1) and level of supplementation of each mixture (3 or 6 mL d -1 ). Control steers had no PAP supplementation. Steers were adapted to the feeding regimen for 14 d, with no PAP supplementation, followed by a 21-d treatment period. Ruminal fluid (RF) from each steer (experimental unit) was collected before PAP supplementation (h 0) and every 4 h (for a 24-h period) on d 0, 14, and 21 of treatment period for the determination of ruminal fermentation profile. In addition, RF collected at h 0 was individually mixed with McDougall's Buffer (1:3 ratio) to inoculate serum bottles and polycarbonate tubes for the determination of methane production and in vitro fermentation profile. Treatment means were evaluated by preplanned, non-orthogonal, single-degree-of-freedom contrasts. There was no effect (P ≥ 0.48) of level of inclusion on ex situ methane production (ESMP). When PAP-M1 was used either alone or in combination with PAP-Ho, ESMP decreased (P ≤ 0.05) compared to control. Ex situ ruminal fermentation profile was not different (P ≥ 0.12) across treatments. In vivo molar proportion of propionate tended to be greater (P = 0.10) with supplementation of PAP-M1, alone or combined, compared with control. Polyclonal antibody preparations against ruminal methanogens have the potential to decrease enteric methane emissions.